Proposta de um sistema de desligamento automático e medição de volume de óleo em um tanque cilíndrico horizontal com extremidade elíptica - OLIVEIRA JUNIOR, Avelino Braz de (2019)
This work is included in the large area of automation, focusing mainly on the context of electronics, it presents a proposal for automation of a field activity in the area of electrical engineering, used the Arduino electronic prototyping platform. Aiming to make a routine activity in the field less tiring, this activity occurs when there is a need to supply a cylindrical tank with elliptical ends, used to store oil while the machine that uses the oil undergoes some maintenance. For the automation it will be necessary to have the knowledge of the dimensions of the tank, which can be easily acquired quantitatively in the field, where it is installed, then will be deduced the formulas for the volume settings according to the parameters involved taking into consideration The horizontal cylindrical tank, acting as a variable to work the height of the liquid contained in the tank. Next, the electronic device implementations, initially the arduino, where basic programming knowledge will become necessary, the electrical part of the circuit was in the assembly of the circuit where the knowledge of electronics was necessary, in the use of the elements of Relays, circuit breakers, test plates, cables, wires, resistors and so on. The evaluation for validity of the test device developed in this work was done in laboratory and theoretical analysis, since it was not implemented in practice in fields, because for this it was necessary a whole bureaucratic process within the company / plant where it was idealized the project.